Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Terhadap Dosis KCl dan Metode Aplikasinya di Pre-Nursery - Moh. Syahrul Munir; Elis Rahmawati Mar`atus Sholihah; Titin Andriyni Atmojo; Getta Hayyuning Mangesti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Oil palm (Elaeis guineensis Jacq.) is an important plantation commodity that makes a significant contribution to Indonesia's economy. One of the macro nutrients that plays a role in supporting plant growth is potassium (K), which is involved in various physiological processes. The effectiveness of nutrient utilization is not only determined by the amount of fertilizer applied but also influenced by the application method, especially during the early seedling phase. This study aims to examine the growth response of oil palm seedlings to variations in KCl fertilizer doses and different fertilizer application methods during the pre-nursery phase. The experiment was arranged using a Factorial Randomized Block Design (RBD) with two treatment factors, namely KCl fertilizer dose and fertilizer application method, each with three replications. The KCl doses consisted of five levels, while the application methods included watering, broadcasting, and localized application (pocket). The observation data were analyzed using analysis of variance and followed by Duncan Multiple Range Test (DMRT) at a 5% level if there were significant differences. The results of the study showed that there was no interaction between the dose of KCl fertilizer and its application method on all observed oil palm seedling growth parameters.